Theory and detection of magnetic monopoles in gauge theories - Craigie, Neil (World Scientific, 1986)
7 chapters: introduction; mathematical structures underlying monopoles in gauge theories; monopoles and their quantum fields; monopoles in cosmology; monopoles and astrophysics; conclusion: prospects in higher dimensions; the experimental detection of magnetic monopoles